2020
DOI: 10.1073/pnas.2002956117
|View full text |Cite
|
Sign up to set email alerts
|

The role of fibril structure and surface hydrophobicity in secondary nucleation of amyloid fibrils

Abstract: Crystals, nanoparticles, and fibrils catalyze the generation of new aggregates on their surface from the same type of monomeric building blocks as the parent assemblies. This secondary nucleation process can be many orders of magnitude faster than primary nucleation. In the case of amyloid fibrils associated with Alzheimer’s disease, this process leads to the multiplication and propagation of aggregates, whereby short-lived oligomeric intermediates cause neurotoxicity. Understanding the catalytic activity is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(100 citation statements)
references
References 50 publications
5
95
0
Order By: Relevance
“…In another recent study also involving the Aβ peptide, several sequence variants were investigated. It was shown that surface cross-nucleation was only efficient if the monomer had an innate preference (as judged from the fibrils formed de novo) for the structure of the seed fibril (Thacker et al, 2020). While these experiments are suggestive of some degree of specificity of fibril surface nucleation, they do not demonstrate the actual transmission of the template structure.…”
Section: Various Point Mutationsmentioning
confidence: 95%
See 2 more Smart Citations
“…In another recent study also involving the Aβ peptide, several sequence variants were investigated. It was shown that surface cross-nucleation was only efficient if the monomer had an innate preference (as judged from the fibrils formed de novo) for the structure of the seed fibril (Thacker et al, 2020). While these experiments are suggestive of some degree of specificity of fibril surface nucleation, they do not demonstrate the actual transmission of the template structure.…”
Section: Various Point Mutationsmentioning
confidence: 95%
“…Cross-surface nucleation was found to be only efficient if monomer has same structural preference as seed fibril (Thacker et al, 2020).…”
Section: Various Point Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary nucleation is catalysed by the surface of pre-existing fibrils [48] , [49] , [50] , [51] , [52] . The properties of the ‘parent’ fibril that facilitate secondary nucleation remain to be established; however, it has been postulated that hydrophobic patches on the fibril surface [53] , and the ability of misfolded monomers to ‘recognize’ similar structures within the ‘parent’ fibril play a role in this process [54] . It was recently shown that decreasing the surface hydrophobicity of fibrils formed by the AD-associated Aβ(1-42) via serine substitution of hydrophobic residues exposed on the fibril surface, does not change the rate of secondary nucleation [53] .…”
Section: Oligomerisation and Kinetics Of Fibril Formationmentioning
confidence: 99%
“…The properties of the ‘parent’ fibril that facilitate secondary nucleation remain to be established; however, it has been postulated that hydrophobic patches on the fibril surface [53] , and the ability of misfolded monomers to ‘recognize’ similar structures within the ‘parent’ fibril play a role in this process [54] . It was recently shown that decreasing the surface hydrophobicity of fibrils formed by the AD-associated Aβ(1-42) via serine substitution of hydrophobic residues exposed on the fibril surface, does not change the rate of secondary nucleation [53] . However, both α-syn [55] and Aβ(1-42) [53] are able to ‘template’ secondary nuclei via the exposed surface residues of the mature fibrils, wherein monomers transiently bind and form oligomers with identical morphologies to those of the templating fibril.…”
Section: Oligomerisation and Kinetics Of Fibril Formationmentioning
confidence: 99%